Head table at the San Jose YWCA annual meeting - Unknown:::Creator::::::::::::
Photograph shows the head table at the San Jose YWCA annual meeting in 1965 with a man standing at the microphone. The women are (left-to-right): Mrs. John Goldsborough, Mrs. Fred May, and Mrs. Sargent (Lucille) Wright, Mrs. Jemimah Gecaga, Kenya YWCA president and, Lois M. Cullison. There is a woman playing piano on the stage behind them